Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/met10010022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Charging on Pop-in Behavior of a Zr-Based Metallic Glass

Abstract: In this work, structural and mechanical properties of hydrogen-charged metallic glass are studied to evaluate the effect of hydrogen on early plasticity. Hydrogen is introduced into samples of a Zr-based (Vit 105) metallic glass using electrochemical charging. Nanoindentation tests reveal a clear increase in modulus and hardness as well as in the load of the first pop-in with increasing hydrogen content. At the same time, the probability of a pop-in occurring decreases, indicating that hydrogen hinders the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…They also showed that H charging decreased the critical stress for pop-in and discussed the effect of a reduction in the elastic self-energy of dislocations for a homogeneous dislocation nucleation model. Tian et al recently reported an interesting experimental study of the effect of H on the mechanical behavior of Zr-based bulk metallic glass (BMG) [ 128 ]. They showed that H charging increased the pop-in critical load, as well as Young’s modulus and the hardness of the BMG material, which is the antithesis of the trend in crystalline materials.…”
Section: Effect Of Pre-existing Lattice Defectsmentioning
confidence: 99%
“…They also showed that H charging decreased the critical stress for pop-in and discussed the effect of a reduction in the elastic self-energy of dislocations for a homogeneous dislocation nucleation model. Tian et al recently reported an interesting experimental study of the effect of H on the mechanical behavior of Zr-based bulk metallic glass (BMG) [ 128 ]. They showed that H charging increased the pop-in critical load, as well as Young’s modulus and the hardness of the BMG material, which is the antithesis of the trend in crystalline materials.…”
Section: Effect Of Pre-existing Lattice Defectsmentioning
confidence: 99%
“…Tian et al [2] studied the structural and mechanical properties of hydrogen-charged metallic glass. They found that nanoindentation reveal a clear increase in the elastic modulus and hardness as well as in the load of the first pop-in with increasing hydrogen content.…”
mentioning
confidence: 99%